Mineral Fertilization Increases Litterfall in Degraded Soils by Arenization - Souza, Huan Pablo de; Malheiros, Angélica Costa; Momolli, Dione Richer; Ludvichak, Aline Aparecida; Guimarães, Claudiney Couto; Gonsalves, José Mateus Wisniewski; Schumacher, Mauro Valdir (Journal of Agricultural Studies, 2021)
Young stands on sandy soils with low natural fertility are more dependent on chemical fertilization. The litterfall becomes the most important route for biogeochemical cycling in an ecosystem. Therefore, the aim of the study was to quantify the annual litterfall, evaluate the seasonality of deposition and verify the litterfall response under different amounts of fertilizers in a young eucalyptus stand implanted in soil degraded by arenization in southern Brazil. Litterfall was evaluated using litter traps with an area of 0.5 m². Fortnightly, over a year, collections and quantification of dry mass were performed. Each of the 5 fertilizer treatments received increasing amounts of nutrients. The litterfall had seasonal pattern, with larger quantities for the spring season, with statistical difference at a level of 5% probability of error from other seasons evaluated, marked by the increase in temperatures. The amount of litterfall, in descending order, followed the amount of nutrients applied in the treatments: T5 > T3 > T4 > T2 > T1. The annual litterfall ranged from 518 to 1326 kg ha-1 of the treatment that received natural phosphate (T1) and triple superphosphate (T5), respectively. This variation represents an increase of 156%. The increase in litterfall is associated with the amount of fertilizers.